EVALUASI TINGKAT PARASITISASI PARASITOID TELUR DAN LARVA TERHADAP PLUTELLA XYLOSTELLA L. (LEPIDOPTERA: YPONOMEUTIDAE) PADA TANAMAN KUBIS-KUBISAN - Nila Wardani dan Amrizal Nazar . (Universitas Lampung, 2002)
Evaluation of parasitization of egg and larvae parasitoids to Putella xylostella L. (Lepidoptera: Yponomeutidae) on crucifers. Diamond back moth Plutella xylostella is an important pest of cabbage in Indonesia. Trichogramma (egg parasitoid) and Diadegma (larvae parasitoid) are the main parasitoid of diamond back moth. This study was conducted as survey methods in several region in West Java. The results indicated that level of parasitism by egg parasitoid (40.45%) was higher than larvae parasitoid (15.98%).